Pancasila Implementation Strategy as Dar al-ahdi wa al-syahadah - Ma'mun Murod; Tria Patrianti; Lusi Andriyani; Usni Usni; Djoni Gunanto (BASKARA : Journal of Business and Entrepreneurship, 2022)
Pancasila has become an agreement as to the final form of state philosophy or ideology. Pancasila is considered a "middle way". Muhammadiyah, as an important actor in the process of formulating Pancasila, feels it is important to maintain Pancasila as the basis of the state. At the 47th Muhammadiyah congress in Makassar, 2015, Muhammadiyah decided to make Pancasila as Dār Al-Ahdi Wa Al-Syahādah. This paper examines the Pancasila Implementation Strategy as Dār Al-Ahdi Wa Al-Syahādah to provide solutions to the ideological and practical problems of Pancasila. There are many challenges facing Pancasila. Some are ideological and some are practical. The ideological challenges are relatively reduced as a result of the commitment of Islamic organizations such as Muhammadiyah to Pancasila. On the other hand, the practical challenges related to the implementation of Pancasila are even greater. For example, Pancasila has played a role in Indonesian economic policies in dealing with COVID-19, business monopolies and oligarchs, and eradicating corruption?. This study uses the Literature Review method for meta-analysis of data by reviewing several articles in national and international journals. The conclusion is that the Pancasila problem is more related to the implementation of the values contained in the Pancasila precepts. The very great values of Pancasila are not able to colour the life of the nation and state.